PP.02.32: DETECTION OF SOMATIZATION RISK IN HYPERTENSION. (June 2015) - De Tettamanzi, M. Cadenas; Maristany, M.; Gomez, B.; Haehenel, M.; Obregon, S.; Brandani, L.; Dulude, E. Perasso; Koretzky, M.; Carrizo, P.; Vaisbuj, F.; Huguet, E.; Chan, D.; et al.
Abstract : Objective: From clinical experience hypertensive patients frequently reported perception of a high prevalence of symptoms that are a priori not linked to hypertension disease itself (headaches, sleep disorders, mood disorders). In this setting, somatization implies not only a health problem due to high-cost of complementary studies and consultations, but it affects patient adherence to treatment. a) to determine the risk of somatization in hypertensive's b) to evaluate association between somatization and antihypertensive drug therapy, c) to analyze distribution of mood disorders such as depression in the population sample. Design and method: We prospectively included 240 individuals who voluntarily complete the measurement instrument SCL-90-R(Hopkins Symptom Checklist-HSCL, Derogatis et ael, 1977–1994) consisting of a symptom scale composed of 90 items grouped into 9 subscales, assigning to each of the items a possible value of 5 points accordingly to subject answer. For the purpose of this study we selected 3 subscales: a) somatization (SOM), b) depression (D) and c) anxiety (ANS). A psychological evaluation by an expert was also provided. Results: After applying the exclusion criteria, final sample was 120 subjects (57.8 years, 50% women).BP history led to the classification in 2 groups, 1) group hypertensive (all with controlled BP at inclusion)(n:68, 131 ± 7. 6 / 76 ± 9 mm Hg), and 2) group normotensive (n: 52, MAP 99.26 ± 8.84 mm Hg.). SCL-90-R score from all population was 113.5 ± 15. 87. The interrelationship between the subscales DEP, SOM, ANS was significant (coef.Spearman, p < 0.0001), while women's and hypertensive's showed a higher prevalence of depression, anxiety and somatization (. Among hypertensives, a significative increase in DEP, SOM and sleep disorders were observed in those under pharmacological treatment (n: 38). Figure. No caption available. Conclusions: In a sample of subjects in primary prevention, the risk of Somatization and related disorders (anxiety and depression) was higher in women, hypertensive and especially in hypertensive patients pharmacologically treated. The possibility of detecting the individualized risk of somatizations across scales validated internationally might promote a special managing of the subject and his manifestations, beside contributing to the comprehension of the symptoms that traditionally attribute the HTA to themselves.